Rancang Bangun Indikator Lifetime Berbasis IoT pada Lampu Terapi Infrared - Hanifan Hiroi Ariyanto; Gema Romadhona; Abdul Latif; Kusnanto Mukti Wibowo; Royan (CYCLOTRON, 2026)
Abstract— Infrared therapy is widely used in medical rehabilitation and physiotherapy services. Infrared therapy lamps have a limited operational lifetime that decreases due to component degradation even though the lamp still appears functional. The main problem is the absence of a system capable of automatically calculating accumulated usage time and providing early warnings before the lamp reaches its service limit. This study aims to evaluate an Internet of Things (IoT)-based lifetime monitoring system for infrared therapy lamps. The research applies an engineering method using a research and development (R&D) approach. Testing was conducted to assess the system’s ability to record operating time and transmit data to an IoT platform in real time. Results show that at testing durations of 8, 10, and 12.5 minutes, the system generated notifications with an average deviation of 0.01 minutes (0.60 seconds) and an error of 0.001%, which is within acceptable tolerance for non-contact medical applications. Therefore, the proposed system is capable of accurately monitoring lamp lifetime and supporting remote preventive maintenance of infrared therapy equipment.